Studies on Area Assessment under Mangroves of Raigad District, Maharashtra, India - Telave, Ajit B.; Ghodake, Shrikant D.; Pawar, Ganesh P. (Indian Forester, 2017)
Mangroves of Maharashtra are under great threat of human enchroachment. The increased pressure over the mangrove habitat degrade the mangrove area. The Raigad district is close to the Mumbai and the activities in Mumbai have the reflections over the Raigad mangroves. In the present work attempt is made to analyse the area occupied by the mangroves in the coastal area of Raigad district and the changes in the mangrove habitat over the period of time using Google Earth Pro images and ground observations. The threats to the mangroves of Raigad were also analysed, it was observed that there is slight decline in the mangrove area in last ten years, 103.80 Km2 in 2005 to 88.09 Km2 in 2015. But, the mangroves are under great threat and continuous urabanization will lead into the destruction of this habitat.